Telecinematic Discourse From Script to Screen: A Corpus-Based Case Study - Chierichetti, Luisa (Círculo de Lingüística Aplicada a la Comunicación, 2025)
This article explores the transition from written text to oral expression in the audiovisual dialogues of the Spanish television series Vis a vis, comparing the original scripts with the dialogues delivered on screen. A corpus-based approach is used to identify linguistic patterns that emphasize emotionally and spontaneity, such as the use of interjections, imperatives, and the periphrastic future. The analysis reveals how the actors’ performances introduce discursive modifications that enhance realism and foster audience empathy, while emplying strategies aimed at humanizing the characters and creating an emotional impact. This study aims to contribute to the analysis of prefabricated oral language in audiovisual fiction, highlighting how the actors’ interpretation amplifies the characters’ inner states through linguistic resources that enhance emotional and persuasive impact on the audience.